Case study. An adult woman with borderline personality structure: an approach from the perspective of dynamic psychology - Tovar Palomino, Diana Yaneth (Pensando Psicología, 2010)
Clinical practice becomes a method of social science research by exposing the particularity and singularitythat characterizes a situation. This paper shows a case study’s result of a woman with limit character disorder, which methodological orientation is focused from object relations’ theory. In-depth interviews, Projective Tests of Thematic Apperception (tat) and Warttegg Test were used as assessment instruments. The results show the characterologic structure of the organization of borderline personality and how this structure influences in significative way the evaluated subject’s current relational dynamic. It was possible to establish that a direct relationship exists between primary emotional links established by this woman and current emotional relationship. These data make possible a better understanding of the functioningof this personality structure and, therefore, providing issues for a therapeutic approach.
Keywords: limit character; character disorder; intrapsychic functioning; object relations; emotional bond